Naproxen chemoprevention induces proliferation of cytotoxic lymphocytes in Lynch Syndrome colorectal mucosa - Bowen, Charles M.; Deng, Nan; Reyes-Uribe, Laura; Parra, Edwin Roger; Rocha, Pedro; Solis, Luisa M.; Wistuba, Ignacio I.; Sepeda, Valerie O.; Vornik, Lana; Perloff, Marjorie; Szabo, Eva; Umar, Asad; et al. (Frontiers in Immunology, 2023)
Background: Recent clinical trial data from Lynch Syndrome (LS) carriers demonstrated that naproxen administered for 6-months is a safe primary chemoprevention that promotes activation of different resident immune cell types without increasing lymphoid cellularity. While intriguing, the precise immune cell types enriched by naproxen remained unanswered. Here, we have utilized cutting-edge technology to elucidate the immune cell types activated by naproxen in mucosal tissue of LS patients. Methods: Normal colorectal mucosa samples (pre- and post-treatment) from a subset of patients enrolled in the randomized and placebo-controlled ‘Naproxen Study’ were obtained and subjected to a tissue microarray followed by image mass cytometry (IMC). IMC data was processed using tissue segmentation and functional markers to ascertain cell type abundance. Computational outputs were then used to quantitatively compare immune cell abundance in pre- and post-naproxen specimens. Results: Using data-driven exploration, unsupervised clustering identified four populations with statistically significant changes between treatment and control groups. These four populations collectively describe a unique cell population of proliferating lymphocytes within mucosal samples from LS patients exposed to naproxen. Conclusions: This study determined that daily naproxen promotes T-cell proliferation in the colonic mucosa, which paves way for developing combination immunoprevention strategies including naproxen for LS patients.